Implementasi Model Pembelajaran Kooperatif Jigsaw Menurunkan Keluhan Muskuloskeletal dan Kebosanan Peserta Didik di SMA - Dewa Made Aris Tian Saputra; Desak Made Citrawathi; I Made Sutajaya (Undiksha, 2020)
The purpose of the study was to prove that the implementation of the Jigsaw cooperative learning model can reduce the musculoskeletal complaints and boredom of students. This study used a nonequivalent randomized pre and posttest control group design, which involved 33 students in the experimental class and 33 students in the control class. Data collection was done through the distribution of Nordic body map questionnaires to record musculoskeletal complaints, and boredom questionnaires to record boredom in the learning process. The data obtained were analyzed by independent sample t test, because the data were normally distributed at a significance level of 5%. The results showed that the implementation of the Jigsaw cooperative learning model significantly reduced musculoskeletal complaints by 46.71% and boredom by 26.76%, between the experimental class and the control class (p <0.05). It can be concluded that the implementation of the Jigsaw cooperative learning model reduces musculoskeletal complaints and boredom of students